Environmental noise and self-rated health in older surgical patients undergoing general anesthesia: a cross-sectional study of anxiety as a behavioral pathway for healthy aging - Shen, Jie; Ma, Hui; Yang, Xiaohui; Hu, Mingcan; Tian, Jieyin; Zhang, Liting (Frontiers in Public Health, 2025)
BackgroundPromoting healthy aging—a core public-health objective—demands hospital environments that support functional recovery and well-being. Excessive ward noise, however, is a modifiable environmental factor that may thwart this goal by amplifying anxiety and diminishing older adults’ self-rated health, yet the magnitude and mechanism of this effect remain poorly quantified.MethodologyWe undertook a cross-sectional survey in March–August 2024 at a tertiary hospital in Hebei Province, China. Continuous bedside monitoring captured 24-h A-weighted equivalent sound levels (LAeq) for 270 surgical in-patients aged ≥ 60 years. Exposure was grouped into quartiles [≤ 45, 45.1–50, 50.1–55, > 55 dB(A)]. Poor self-rated health (SRH, scores 1–3/5) and anxiety (Generalized Anxiety Disorder-7) were assessed concurrently. Hierarchical logistic models estimated associations per 5 dB(A) increment; bias-corrected bootstrap mediation quantified the proportion of the noise–health relation transmitted through anxiety.ResultsMedian LAeq was 52.1 dB(A), well above the WHO daytime limit of 35 dB(A). The prevalence of poor SRH rose from 28% in the quietest quartile to 58% in the noisiest (p < 0.001). After adjustment for demographic, socioeconomic, clinical and ward factors, each 5 dB(A) increase in LAeq raised the odds of poor SRH by 16% (OR = 1.16, 95% CI 1.00–1.33, p = 0.047). Anxiety independently predicted poor SRH (OR = 1.10 per GAD-7 point) and mediated 23% of the total noise effect (indirect β = 0.048, 95% CI 0.019–0.086, p = 0.002).ConclusionHospital sound levels substantially above international guidelines constitute a modifiable environmental barrier to healthy aging, deteriorating older adults’ self-perceived health partly by intensifying anxiety. Integrating acoustic standards into hospital quality metrics and coupling noise reduction with early anxiety management represent feasible public-health strategies to support functional recovery and well-being in rapidly aging populations.